Literature and philosophy in Nineteenth Century British culture.
1 online resource (510 pages)
Keywords: This three-volume collection of primary sources examines philosophy and literature in the nineteenth-century Britain. Accompanied by extensive editorial commentary, this collection will be of great interest to students and scholars of British Literature and Philosophy.